Hubungan Antara Strategi Coping Dengan Stres Akademik Pada Mahasiswa Yang Menjalin Hubungan Asmara Di Surabaya Dengan Dukungan Sosial Sebagai Variabel Moderator - Indra Karunia Akbar Putra Harmiko; IGAA Noviekayati; Muchammad Rizal; Amherstia Pasca Rina (Universitas Nahdlatul Ulama Blitar, 2026)
Academic stress is a form of psychological pressure frequently experienced by university students due to demanding academic responsibilities, especially among students in early adulthood who are involved in romantic relationships. To manage these pressures effectively, students need adaptive coping strategies. In addition, social support is considered an important factor that can help students deal with academic stress through emotional and instrumental assistance. This study aimed to examine the relationship between coping strategies and academic stress among university students in romantic relationships in Surabaya, as well as to investigate the moderating role of social support in this relationship. The study employed a quantitative correlational design involving 167 university students from several higher education institutions in Surabaya who were currently in romantic relationships. Data were collected using coping strategies, academic stress, and social support scales based on the theories of Lazarus and Folkman (1984), Bedewy and Gabriel (2015), and Sarafino and Smith (2014). Data analysis was conducted using Moderated Regression Analysis (MRA). The findings revealed a significant relationship between coping strategies and academic stress. Moreover, social support significantly moderated this relationship by helping students optimize coping strategies when facing academic demands.